Differences in sodium fluoride-18 uptake in the normal skeleton depending on the location and characteristics of the bone - Nawata, Shintaro; Kaneta, Tomohiro; Ogawa, Matsuyoshi; Ishiwata, Yoshinobu; Kobayashi, Naomi; Shishikura-Hino, Ayako; Yoshida, Keisuke; Inaba, Yutaka; Saito, Tomoyuki; Inoue, Tomio (Nuklearmedizin - NuclearMedicine, 2017)
Aim: The aim of this study was to evaluate the normal distribution of sodium fluoride-18 (NaF-18) and to clarify the differences in uptake according to location and the type of the bone using positron emission tomography (PET) / computed tomography (CT). Methods: We retrospectively reviewed NaF-18 PET/CT images from 30 patients with hip joint disorders. PET/CT scans were performed 40 min after injection of approximately 185 MBq of NaF-18. To evaluate the relationship between the distribution of NaF-18 uptake and bone density, we compared the maximum standardised uptake values (SUVmax) on PET and the Hounsfield Units (HUs) on CT of the lumbar vertebra, ilium, and proximal and distal femurs. Regions of interests were defined both outside and inside the cortical bone to measure whole bone and cancellous bone only, respectively. Results: The distribution of NaF-18 differed according to the skeletal site. The lumbar vertebra showed the highest SUVmax for both whole bone and cancellous bone, followed by the ilium, proximal femur, and distal femur. The bones differed significantly in SUVmax. The distal femur showed the highest HU, followed by the proximal femur, ilium, and vertebra. Profile curve analyses demonstrated that the cancellous bones showed higher SUVmax and lower HU than the cortical bones. Conclusions: Our results demonstrate the difference in NaF-18 uptake between cancellous and cortical bones, which may explain differences in uptake by location. NaF-18 uptake does not appear to be strongly correlated with bone density, but rather with bone turnover and blood flow.
Keywords: Sodium fluoride; NaF; PET; SUV; bone imaging